2021
DOI: 10.21203/rs.3.rs-103140/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge and understanding of obstetric danger signs among pregnant women attending the antenatal clinic at the National Referral Hospital in Thimphu, Bhutan: a cross-sectional study

Abstract: Background: The third Sustainable Development Goal for 2030 development agenda aims to reduce maternal and newborn deaths. Pregnant women’s understanding of danger signs is an important factor in seeking timely care during emergencies. We assessed knowledge of obstetric danger signs using both recall and understanding of appropriate action required during obstetric emergencies. Methods: This was a cross-sectional study among pregnant women attending antenatal clinic at Bhutan’s largest hospital in Thimphu. Rec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…This was also supported by Ijang et al who reported that knowledge of Obstetric danger signs was associated with the practice of BPCR among pregnant women [10]. More importantly, good knowledge of obstetric dangers signs in pregnancy has been indicated as one of the factors promoting complication readiness as well as receiving timely emergency obstetric care [21]. Therefore, many pregnant women will still benefit from awareness programs and other interventions to raise awareness of these obstetric danger signs among pregnant women.…”
Section: Discussionmentioning
confidence: 67%
“…This was also supported by Ijang et al who reported that knowledge of Obstetric danger signs was associated with the practice of BPCR among pregnant women [10]. More importantly, good knowledge of obstetric dangers signs in pregnancy has been indicated as one of the factors promoting complication readiness as well as receiving timely emergency obstetric care [21]. Therefore, many pregnant women will still benefit from awareness programs and other interventions to raise awareness of these obstetric danger signs among pregnant women.…”
Section: Discussionmentioning
confidence: 67%
“…Según el estudio de Pembe A et al 18 , ellos también determinaron que el estado civil no tiene asociación, resultado que difiere de nuestro estudio; pero el nivel educativo sí difiere, pues ellos refieren que a mayor nivel escolar mayor conocimiento y por ende una mejor actitud sobre signos y síntomas de alarma. Ambas variables se consideran estadísticamente significativas en los estudios de Nebiyu Maseresha et al 19 y Tamang ST et al 20 , lo cual difiere parcialmente a los datos encontrados en nuestro estudio.…”
Section: Discussionunclassified
“…Posteriormente, se realizó el mismo análisis con la variable nivel de conocimiento, encontrándose una asociación estadísticamente significativa con las variables estado civil (RP 0,15, IC95% 1,09-1,20, p<0,001) y paciente añosa (RP 0,96, IC95% 0,89-1,04, p<0,001). Similares resultados vemos en Amenu et al 15 y Tamang ST et al 20 donde la variable presentar pareja se convierte en una asociación favorable para un alto nivel de conocimiento.…”
Section: Discussionunclassified